PERAN METODE PEMBELAJARAN DAN GAYA BELAJAR TERHADAP PENINGKATAN PEMAHAMAN KONSEP IPA SISWA DALAM KONTEKS PENDIDIKAN SOSIAL - Evi Tri Asmita; Natasya Aribah; Salsabila Khairani Batubara; Sri Devi Wahyuni; Mira Andriyani (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2025)
This study aims to determine the effect of learning methods and learning styles on the understanding of science concepts in fifth-grade students at MIS Widyatul Hasanah. The study used a quasi-experimental method with a 2x2 treatment-by-level design. The research instruments consisted of conceptual understanding tests (multiple-choice and descriptive) and a learning style questionnaire. The results showed that: (1) students' understanding of science concepts using active demonstration-based learning methods was higher than those using conventional learning methods; (2) there was an interaction between learning methods and learning styles on understanding of science concepts; (3) students with visual learning styles had higher conceptual understanding when using demonstration methods; (4) students with auditory learning styles had higher conceptual understanding when using conventional learning methods.